en - Dan Dan, Liu; Xing, Lu; Septevany, Elvira (e-Journal of Linguistics; Vol 17 No 1 (2023): en, 2022)
As a tool for legal spelling and phonetic transcription of Chinese,  the Chinese Pinyin System Scheme  is an indispensable tool for international Chinese teaching. International Chinese teachers should systematically understand it in theory, pay attention to some details in the teaching of Chinese Phonetic Alphabet, improve the teaching effect of Chinese Phonetic Alphabet, and avoid detours.